2008
DOI: 10.1074/jbc.m800233200
|View full text |Cite
|
Sign up to set email alerts
|

Modified Uridines with C5-methylene Substituents at the First Position of the tRNA Anticodon Stabilize U·G Wobble Pairing during Decoding

Abstract: Post-transcriptional modifications at the first (wobble) position of the tRNA anticodon participate in precise decoding of the genetic code. To decode codons that end in a purine (R) (i.e. NNR), tRNAs frequently utilize 5-methyluridine derivatives (xm 5 U) at the wobble position. However, the functional properties of the C5-substituents of xm 5 U in codon recognition remain elusive. We previously found that mitochondrial tRNAs Leu(UUR) with pathogenic point mutations isolated from MELAS (mitochondrial myopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
116
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 60 publications
5
116
0
1
Order By: Relevance
“…For instance, pseudouridine at position 32 uses a water mediated base-backbone interaction to stabilize the interaction between nucleosides 32 and 38. 138 While a stronger interaction, like that of a canonical base pair at this position could lead to a loss in flexibility of the loop domain, a weaker interaction could result in loss of stacking in the ASL resulting in a disruption of the functional U-turn conformation of the ASL. Modifications at the 32 nd and 38 th positions of the ASL may be important as a possible means of modulating the interaction between the two nucleosides and base stacking in the loop.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, pseudouridine at position 32 uses a water mediated base-backbone interaction to stabilize the interaction between nucleosides 32 and 38. 138 While a stronger interaction, like that of a canonical base pair at this position could lead to a loss in flexibility of the loop domain, a weaker interaction could result in loss of stacking in the ASL resulting in a disruption of the functional U-turn conformation of the ASL. Modifications at the 32 nd and 38 th positions of the ASL may be important as a possible means of modulating the interaction between the two nucleosides and base stacking in the loop.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that the m 5 U modification in human mt tRNA Leu (UUR) stabilizes the m 5 U:G wobble pairing at the ribosomal A site during decoding (29). A structural study of the ribosomal 30S subunit containing codon-anticodon pairing at the A-site provided a mechanistic explanation for the manner in which the 5-taurinomethyl modification enables efficient decoding of G-ending codons (30). In the human mitochondrial decoding system, m 5 (s 2 )U is found in five tRNAs for Leu(UUR), Trp, Lys, Glu, and Gln (23,24,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…One reaction involves the detoxification of hypochlorous acid by taurine resulting in the formation of taurine chloramine, a product that has the added benefit of possessing anti-inflammatory activity (Schuller-Levis and Park 2003;Marcinkiewicz and Kontny 2013;Kim and Cha 2014). Taurine also forms a conjugate (5-taurinomethyluridine) with the wobble position uridine of tRNA Leu(UUR) , a reaction that enhances the interaction between the modified uridine and guanine (Kirino et al 2005;Kurata et al 2008;Schaffer et al 2013). Biochemically, this enhances the binding of the UUG codon to the taurine-modified AAU anticodon of tRNA Leu(UUR) , facilitating UUG decoding.…”
Section: Introductionmentioning
confidence: 99%
“…These fundamental biochemical events are defective in the mitochondrial disease, mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes (MELAS), which is caused by one of several tRNA Leu(UUR) mutations. One of the major biochemical abnormalities of the tRNA Leu(UUR) mutations is decreased formation of 5-taurinomethyluridine in the wobble position of tRNALeu(UUR) (Kirino et al 2005;Kurata et al 2008). Because taurine conjugation enhances the interaction of the UUG codon with the taurine-modified AAU anticodon of tRNA Leu(UUR) , the synthesis of mitochondria encoded proteins, such as ND6, is highly dependent upon the 5-taurinomethyluridine modification (Jong et al 2012).…”
Section: Introductionmentioning
confidence: 99%